Puerarin Increases Survival and Protects Against Organ Injury by Suppressing NF-κB/JNK Signaling in Experimental Sepsis - Wang, Lei; Liang, Qiao; Lin, Anqi; Chen, Xiufang; Wu, Yongzhen; Zhang, Bin; Zhang, Yu; Min, Haiyan; Wen, Yanting; Song, Shiyu; Gao, Qian (Frontiers in Pharmacology, 2020)
Puerarin an isoflavonoid rich in Radix Puerariae has been reported to be a broadly effective regulator in various biological processes and clinic conditions. However, the role of puerarin in sepsis-induced mortality with multiple-organ injury remains unknown. Herein, we showed that puerarin potently attenuated organ injury and increased the survival rate in lipopolysaccharides (LPS), as well as cecal ligation and puncture (CLP), induced mouse sepsis models by greatly suppressed pro-inflammatory responses both systemically and locally. In the liver, puerarin inhibited hepatocyte inflammation and TNF-α induced apoptosis. Systemically, puerarin settled overall inflammation mainly by normalizing expanded macrophages in the circulation in sepsis mice. Mechanistically, puerarin directly promoted an M2 phenotype in LPS-stimulated macrophages through the inhibition of NF-κB/JNK pathway. In conclusion, puerarin reduced systemic inflammation and protected organ injury in sepsis mice, thus, it may provide a new modality for better treatment of sepsis.